Introduction to health and safety at work for the NEBOSH national general certificate in occupational health and safety - Hughes, Phil (Phillip W.) 1946-; Ferrett, Ed (Routledge, 2021)
Introduction to Health and Safety at Work covers the fundamentals of occupational safety and health for the thousands of students who complete the NEBOSH National General Certificate in Occupational Health and Safety each year. This 7th Edition closely follows the NEBOSH National General Certificate syllabus which was updated in 2019 and comes into use in 2020. The highly illustrated content covers all of the essential elements of health and safety management, the legal framework, risk assessment and control standards and also includes checklists, report forms and record sheets to supplement learning. It also has an extensive summary of current health and safety legislation. Aligned to the NEBOSH National General Certificate in Occupational Health and Safety Practice questions and answers to test knowledge and increase understanding Complete with a companion website containing extra resources for tutors and students The book is suitable for all students following a level 3 Health and Safety course and a source of reference and guidance for managers at work in the UK. Written by renowned authors, this book is often provided as part of the Certificate course and is essential reading for a student.